Home gardening in sub‐Saharan Africa: A scoping review on practices and nutrition outcomes in rural Burkina Faso and Kenya. (25th May 2022) - Hansen, Lea‐Sophie; Sorgho, Raissa; Mank, Isabel; Nayna Schwerdtle, Patricia; Agure, Erick; Bärnighausen, Till; Danquah, Ina
Abstract: Home gardening is promoted as an adaptation strategy to ameliorate the increasing food insecurity from climate change impacts among subsistence farming families in rural sub‐Saharan Africa. Yet, the geographic distribution of home gardens, their setup, management, and the effects on nutrition outcomes have not been fully described. This scoping review aimed to map and synthesize recent evidence on home gardening for two exemplar countries: Burkina Faso and Kenya. Between June and August 2020, we searched, screened, and extracted evidence about home garden projects in both countries, following the PRISMA guidelines for scoping reviews. Peer‐reviewed scientific publications, and gray literature in English and French that reported about subsistence horticulture in rural settings of Burkina Faso or Kenya were included. The characteristics of the documents and the data pertaining to our research objectives were extracted into predefined spreadsheets. The data were synthesized in the form of a narrative review. Our search yielded 949 documents, of which 20 documents were included in the synthesis (Burkina Faso: 8, Kenya: 12). While the gardens varied in composition and size, the majority provided green leafy vegetables and indigenous horticultural crops. The challenges for successful home garden implementation comprised unfavorable climatic conditions, access to and affordability of inputs, water and land, and lack of know‐how. We identified trends for improved food security, diet quality, and nutritional status among the target populations. This scoping review found that there is limited evidence on home garden practices in rural Burkina Faso and Kenya. To enhance the sustainability of home gardens, research and resources should be invested in codesigning context‐specific home gardening projects. Pending rigorous impact evaluation, home gardens appear to be a promising tool for climate change adaptation while simultaneously improving food security and the nutritional situation among women and young children in these two exemplar countries of sub‐Saharan Africa. Abstract : Home gardening is promoted as an adaptation strategy to ameliorate the increasing food insecurity from climate change impacts among subsistence farming families in rural sub‐Saharan Africa. This scoping review aimed to map and synthesise recent evidence on home gardening for two exemplar countries: Burkina Faso and Kenya. Pending rigorous impact evaluation of home gardening projects, we identified trends for improved food security, diet quality, and nutritional status among women and young children in these two exemplar countries of sub‐Saharan Africa.